The Effect Of Using Image Media and Vocabulary Mastery on Narrative Composition Ability in Elementary School Students - Mardiana Mardiana; Wayan Satria Jaya; Eny Dwi Marcela (IJLHE: International Journal of Language, Humanities, and Education, 2021)
The purpose of this study is to find out the effect of using image media and vocabulary mastery on narrative composition ability in Elementary School students. The method used in this study is the experimental method. The population in this study was students in class V of SDN 1 Labuhan in a total of 127 people divided into 3 classes. The classes used as research samples are VA class as experiment, VB class as control and VC class as instrument trial class. The sampling technique in this study is a random sampling technique. The researcher's data analysis uses the t test and an ANAVA variance analysis. The results of this study are (1) there is a difference in the ability to make up narratives of students who learn to use image media and students who learn to use audio media research data shows a score of 2,263 with a significant 0.026 < 0.05, (2) there is a difference in the ability to make up narratives in the group of students who master high vocabulary between learning to use image media and using audio media (sound) Based on calculations, obtained experiments with a significant count of 0.031 and a t table of 1.761 at a significant level of 0.05. Because the calculation > t table and a significant level of 0.031< 0.05, (3) there is a difference in the ability to make up narratives in groups of students who master low vocabulary, between those who learn to use image media and use audio media (sound), and (4) there is an interaction of the use of image media and mastery of student vocabulary with the ability to make up student narratives. Therefore, the researchers concluded that there is an interaction between the use of image media and the mastery of student vocabulary to the ability to make up student narratives.